The Function of Language as an Adaptation Strategy for Javanese Transmigrants in Simpang Nangka Village, Selupu Rejang District, Bengkulu Province - Rusdi, Muhammad Usaid Ghifari; Kahanna, Mutia; Oktayanty, Yetty (Kirana Publisher (KNPub), 2024)
This research is entitled